Molecular investigation of waterborne protozoan contamination using marine Demospongiae - Boughattas, Sonia; Al-Khater, Albandari; Albatesh, Dana; Giraldes, Bruno W; Abu-Madi, Marawan; Althani, Asma A.; Benslimane, Fatiha M. (Ecological indicators, 2024)
[Display omitted] •Waterborne protozoan pathogens (WBPP) are considerable global burden.•Sponges are potential ecological biomonitors for water safety surveillance.•First molecular report of Blastocystis sp. and Dientamoeba fragilis isolated from marine sponge. Sponges play important role within aquatic ecosystems due to their diverse abilities including filter-based feeding mechanisms. Hence, this study evaluated the potential use of sponges as ecological biomonitors for water safety surveillance, especially in the presence of Waterborne protozoan pathogens WBPP. Sponge specimens were collected from different Qatari marine ecosystems and subjected to gDNA extraction and real-time PCR using specific primer sets for the most common WBPP. Two sponges from the coastal marine ecosystems were found to be positive for Blastocystis sp., and one sponge was positive for Dientamoeba fragilis within offshore site. No Cryptosporidium spp., Giardia duodenalis, nor Toxoplasma gondii were detected. Further genotyping analysis revealed that the Blastocystis sp. positive samples were subtype ST3 (allele 34), which matched local clinical isolates and D. fragilis specimen was unambiguously clustering with Genotype 2. In conclusion, this study demonstrates the role of marine sponges as ecological biomonitors for WBPP screening and provide insights into these pathogens widespread and their potential transmission to marine and terrestrial organisms including human.